Thermal Conductivity of Hemp Based Boards (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Energy and raw material costs, an increase in environmental pollution, greenhouse gas emissions, global warming, depletion of fossil raw materials stimulate to seek and study alternatives to the synthetic fibers and products made of them for full or partial replacement. Renewable raw materials, including natural fiber sources, are the future of storage resources with a variety of positive effects on both the planet ecosystem and the living and working environment, and the energy consumption of delivering the required functionality. One of the most important energy-saving types is to reduce energy consumption in buildings by insulating them.For Latvian conditions suitable crops are historically grown flax and hemp. Within the framework of the studies, hemp stems are being used. Hemp compared with flax, are less suffering from diseases and less damaged by pests, so hemp cultivation is practically free from use of chemical pesticides and herbicides reducing the risk to the ecosystem.One of the most frequently mentioned industrial hemp raw materials positive qualities are their very wide use, practically all plant parts can be used in production of different products. This work explores the possibilities and technologies within the Latvian grown hemp stems to work into board materials with insulation capability.Hemp fibers/shives mix boards can fulfill the main function of insulation materials, i.e., to reduce the transmission of heat, because they have a porous structure and low density. Material thermal insulation properties affect physical and structural properties of compounds. Cost effective particles board samples from chopped hemp stems with three types of adhesives and different thicknesses were produced and their thermal conductivity evaluated. The technologies applied and test results will be discussed in the paper.